Water allocation plan on part of Cisadane catchment in the district and city of Bogor - Rias Sholihah; Bambang Dwi Dasanto; Hendarti Hendarti (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
The growth population every year in Bogor caused changes in land use and increased water demand in the Cisadane river basin. The purpose of this study is to analyze the water demand DMI, water availability, water balance and and to evaluate the scope of services on the present and future. Therefore, it is necessary to manage the allocation of water demand by using software DSS (Decision Support System), RIBASIM (River Basin Simulation). The data used in this study are : rainfall, irrigation, population and schematization (Schema of water allocation). This study used base time fram from 2015 - 2030 which refers to the 6 Cis project. The results of the analysis of the model, indicating that the water demand is dominated by DMI (Domestic, Municipal and Industry). In general, the existing surface water sources in most Cisadane river basin can meet various needs, but, because of the priority water demand is for the people, the scope of services (coverage) is a major concern; in this case, lack of water services to the District and City of Bogor was found, as indicated in graphic water demand of DMI (domestic, municipal, industrial) with SIPA (license of water extraction) in 2015 and 2030. Based on the obtained information that is required for optimalised scope of services water supply for the district and the city of Bogor in 2030.